2017
DOI: 10.15344/2456-4028/2017/123
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium L-3 in Eradication of Helicobacter pylori: In-vivo and In-vitro

Abstract: Usage of probiotics as component of anti-helicobacter therapy had been recently approved as a promising trend in the clinical practice. Over the years, we observed high efficacy of probiotic multi bacteriocinogenic strain Enterococcus faecium L-3 as an additional component of the standard triple therapy in eradication of Helicobacter pylori (H.p.) in patients with chronic gastritis associated with H. pylori infection. The cultivation of H.p. in the presence of live probiotic cultures of E. faecium L-3, Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…In an in vitro study conducted by our team, it was observed that the inhibition of H. pylori growth occurred in 50% of cases in contact with a probiotic based on Bacillus subtilis , 78.6% of cases in contact with Enterococcus faecium strain L-3, and 64% of cases in contact with a combination of Bifidobacterium longum and Enterococcus faecium [ 83 ]. In an in vivo study, monotherapy with Enterococcus faecium strain L-3 in patients with chronic gastritis associated with H. pylori showed an eradication rate of 39%[ 84 ].…”
Section: Probiotic Monotherapymentioning
confidence: 99%
“…In an in vitro study conducted by our team, it was observed that the inhibition of H. pylori growth occurred in 50% of cases in contact with a probiotic based on Bacillus subtilis , 78.6% of cases in contact with Enterococcus faecium strain L-3, and 64% of cases in contact with a combination of Bifidobacterium longum and Enterococcus faecium [ 83 ]. In an in vivo study, monotherapy with Enterococcus faecium strain L-3 in patients with chronic gastritis associated with H. pylori showed an eradication rate of 39%[ 84 ].…”
Section: Probiotic Monotherapymentioning
confidence: 99%
“…При этом в эксперименте in vivo эта способность E. faecium L3. была существенно выше, чем у Escherichia coli M17 и Lactobacillus plantarum 8R-A3 [44]. В недавнем исследовании, представленном итальянскими микробиологами была показана бактериостатическая и бактерицидная активность против H. pylori пяти штаммов пробиотиков, при этом наибольшие ингибирующие свой ства выявлены у L. casei, L. paracasei и L. acidofi lus [45].…”
unclassified